IMPLEMENTATION OF INCLUSIVE CLASSROOMS IN THE EARLY CHILDHOOD CONTEXT - Anjaliani, Lidia; Fitriani, Dewi; Muluk, Safrul (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2024)
The implementation of inclusive education is an encouragement to provide the widest possible opportunities or access for all children to obtain quality education by students' individual needs without discrimination. PAUD Harsya Ceria has its own identity, which is different from other schools and requires children to respect each other. PAUD Harsya Ceria has students with special needs who are treated with the principle all children will be accepted regardless of their conditions and uniqueness. This research aims to determine how inclusive classrooms are implemented at PAUD Harsya Ceria. This research uses qualitative descriptive study, and data collection is carried out using interviews, observation, and documentation techniques on how teachers manage and arrange inclusive classrooms. The data analysis technique uses data reduction, data presentation, and conclusion. The findings show that the same curriculum is used in the school for all children, with the differentiation of playing activities to accommodate students with special needs. Materials used are also selected to suit the students. PAUD Harsya Ceria used special guidelines called the kayang strategy to train teacher assistants in carrying out their duties.